PENGARUH MODEL PEMBELAJARAN TERPADU DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN MENULIS DESKRIPSI - Laksitarini, Niken (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: The research is to obtain information concerning to the effect of integrated learning model and independent learning to descriptive writing skill. The research was conducted by using experiment model with design factorial 2x2 analysis in testing hypothesis. In this research, 22 from 80 student’s cluster random sampling. The research was focused on three aspects; integrated learning model and independent learning to descriptive writing skill. The data were collected with test descriptive writing and analyzed with path analysis. Result on the analysis it is concluded that (1) descriptive writing skill students are given the models of learning thematic integrated is higher than students who were given fragmented, (2) Descriptive writing skill student in the group of students who have independent learning high given integrated learning models thematic integrated is greater rather than a group of students were given learning fragmented, (3) Descriptive writing skill student in the group of students who have independent learning low given about learning fragmented is higher than the group of students were given about the model of learning thematic integrated, (4) there is an interaction between learning and independent learning to the descriptive writing skillKeywords: Descriptive Writing Skill, Integrated Learning Model, Independent LearningAbstrak: Penelitian ini adalah untuk mendapatkan informasi mengenai efek dari model pembelajaran terpadu dan belajar mandiri untuk kemampuan menulis deskriptif. Penelitian ini dilakukan dengan menggunakan model eksperimen dengan desain analisis faktorial 2x2 di pengujian hipotesis. Dalam penelitian ini, 22 dari cluster random sampling 80 siswa. Penelitian ini difokuskan pada tiga aspek; model pembelajaran terpadu dan belajar mandiri untuk kemampuan menulis deskriptif. Data dikumpulkan dengan tes menulis deskriptif dan dianalisis dengan analisis jalur. Hasil analisis dapat disimpulkan bahwa (1) menulis deskriptif siswa keterampilan diberi model pembelajaran tematik terpadu lebih tinggi dari siswa yang diberi terfragmentasi, (2) menulis deskriptif siswa keterampilan dalam kelompok siswa yang telah independen pembelajaran tinggi diberikan model pembelajaran terpadu tematik terpadu lebih besar daripada sekelompok siswa diberi pembelajaran terfragmentasi, (3) siswa kemampuan menulis deskriptif dalam kelompok siswa yang memiliki belajar mandiri rendah mengingat tentang belajar terfragmentasi lebih tinggi dari kelompok siswa diberi tentang model pembelajaran tematik terpadu, (4) ada interaksi antara pembelajaran dan belajar mandiri dengan keterampilan menulis deskriptif Kata kunci: Deskriptif Menulis Keterampilan, Model Pembelajaran Terpadu, Pembelajaran Independen